LED color temperature and its effect on the growth of hydroponic lettuce seedlings - Shaw, J. (The Young Researcher)
Previous research has shown that differences in light quality can have profound effects on the growth of hydroponic lettuce. This experiment attempts to determine the correlation between the colour temperature of LED grow lights and the growth of hydroponic lettuce. Initially, this study exposed a total of 252 Butterhead lettuce seedlings to various temperatures of white LED lights to determine if there was any correlation between the warmth of light emitted and the growth of lettuce seedlings. Growth was measured in four variables: height, number of leaves, wet mass, and dry mass. When harvested at 28 days, the results suggest that there is a statistically significant difference between plants grown under 3,000K and 6,000K conditions, with results showing as much as a 232% increase in growth for plants grown under 6,000K lights.